Waiting for the sky to fall : the age of verticality in American narrative - Mackay, Ruth, 1985- (The Ohio State University Press, 2016)
"Waiting for the Sky to Fall: The Age of Verticality in American Narrative by Ruth Mackay traces the figures of flight, grievous falls, and collapsing towers, all of which haunt American narratives before and after 9/11. Mackay examines how these events prefigure 9/11, exploring the narrative residue left by the "end" of horizontal space--when settlers reached America's Pacific Coast, leaving nowhere westward on the continent to go. She then continues into the aftermath of the fall of the Twin Towers. This period of time marks an era of verticality: an age that offers a transformed concept of the limits of space, entwined with a sense of anxiety and trepidation."